Systematic Literature Review: Civic Engagement dalam konteks Digital Citizenship - Alvinca, Muhammad Fikri; Suyato (Information Technology Education Department, 2025)
Civic engagement includes social and political dimensions, and the two dimensions are interrelated in line with this. In this study, the author uses the Scientific Procedures and Rationales for Systematic Literature Reviews protocol (SPAR-4-SLR). In the protocol, there are three stages and six sub-stages. The stages consist of Assembling, Arranging, and Assessing, and the sub-stages consist of Identification, Acquisition, Organization, Purification, Evaluation, and Reporting. Furthermore, the author used thematic, descriptive, and bibliometric analysis techniques. In bibliometric analysis, the author used the VOSviewer application version 1.6.20. The study's results using the Systematic Literature Review (SLR) method using the SPAR-4-SLR protocol show the breadth of research developments related to digital citizenship and civic engagement in various topics and various types of studies or methods. The diversity of country and institutional backgrounds of the authors of articles related to Digital Citizenship and Civic Engagement from each article also shows the broad interest value in the category.